2017
DOI: 10.1016/j.tourman.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Linking the dots among destination images, place attachment, and revisit intentions: A study among British and Russian tourists

Abstract: Limited evidence suggests that the incorporation of both image components (cognitive, affective, and conative) and holistic image is meaningful for predicting tourists' revisit intentions. Extending this line of research, the present study aims to unravel the relative influence that each component of image has directly and indirectly, via holistic image, on revisit intentions. In doing so, we incorporate two national samples (British and Russians) of diverse tourist profile and significantly different levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
160
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(204 citation statements)
references
References 117 publications
(141 reference statements)
11
160
0
5
Order By: Relevance
“…In previous studies, scholars have shown that the overall image of destination not only plays a role in the selection of tourists choosing a destination, but also affects the behavior of tourists in the future. Stylos et al (2017) studies and confirms that there is a significant positive impact between city image evaluations and the visitors' potential behavior intentions.…”
Section: Relationship Between City Brand Image and Visitor's Behaviorsupporting
confidence: 65%
“…In previous studies, scholars have shown that the overall image of destination not only plays a role in the selection of tourists choosing a destination, but also affects the behavior of tourists in the future. Stylos et al (2017) studies and confirms that there is a significant positive impact between city image evaluations and the visitors' potential behavior intentions.…”
Section: Relationship Between City Brand Image and Visitor's Behaviorsupporting
confidence: 65%
“…First, the revisit intention construct is relevant because it is the central element of loyalty (Oppermann, ) and, consequently, of the predisposition to return to a destination (Loureiro, ). Thus, this behavior has attracted the attention of academics and practitioners (Stylos, Bellou, Andronikidis, & Vassiliadis, ) because it is a central element of achieving financial objectives in the tourism context (Oppermann, ).…”
Section: Discussionmentioning
confidence: 99%
“…This could also attract the interest of new hosts to list their properties in Airbnb Inc. The findings could enhance the review system of the Airbnb platform, thus emphasizing the quality indicators that define satisfaction and ultimately loyalty, with the latter widely considered as a proxy of actual tourists' behavior (Stylos, Bellou, Andronikidis, & Vassiliadis, 2017).…”
mentioning
confidence: 90%